Potential differences in somatosensory function during premenopause and early and late postmenopause in patients with burning mouth syndrome: An observational case–control study - Kana Ozasa; Noboru Noma; Andrew Young; Olga A. Korczeniewska; Eli Eliav; Yoshiki Imamura (Journal of Dental Sciences, 2022)
Background/purpose: Burning mouth syndrome (BMS) is a chronic condition presenting as intraoral burning or dysesthesia, with a high preponderance in menopausal women. This study aimed to examine the association between somatosensory dysfunction and BMS in premenopausal, early postmenopausal, and late postmenopausal patients, using a standardized Quantitative Sensory Testing (QST) protocol, and to determine the predictive value of thermal or mechanical perception by QST for detecting BMS. Materials and methods: An observational case–control study was performed with 36 female participants with BMS (12 premenopausal, 10 early postmenopausal, and 14 late postmenopausal) and 42 age- and sex-matched healthy volunteers (21 premenopausal, 10 early postmenopausal, and 11 late postmenopausal). Neurophysiological tests were used to evaluate somatosensory dysfunction at the tongue. Results: Z-score in the late postmenopausal BMS group revealed a gain of function for the cold pain threshold and heat pain threshold (Z = 2.08 and 3.38, respectively). In the multiple regression analysis with the Visual Analog Scale as the dependent variable, the vibration detection threshold predicted the severity of burning mouth sensation in the premenopausal group. Conclusion: Late postmenopausal patients with BMS showed an increased response of the tongue to noxious thermal stimuli. This supports the theory that changes in sex hormones may affect trigeminal somatosensory function, particularly during the late postmenopausal stage in patients with BMS.